1999
DOI: 10.1002/(sici)1097-0215(19991008)83:2<210::aid-ijc11>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Identification of distinct regions of allelic loss on chromosome 13q in nasopharyngeal cancer from paraffin embedded tissues

Abstract: Our main purpose was to identify tumor suppressor gene loci on chromosome 13 responsible for nasopharyngeal cancer (NPC) development by analyzing loss of heterozygosity (LOH) and RB protein expression in paraffin embedded tissues. Normal and tumor DNA were extracted from microdissected samples, and their whole genomes were amplified using degenerate oligonucleotide primers. The polymerase chain reaction (PCR) products were analyzed by repeated amplification using primers derived from 16 microsatellite regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Previous reports showed that environmental factors such as the intake of salted food, Epstein-Barr Virus (EBV) infection, and the function of genetic factors were thought to be important in the etiology of NPC [3]. Loss of heterozygosity (LOH) studies unveiled there are frequent allelic losses on chromosomes 3p, 9p, 11q, 13q, and 14q in NPC [4][5][6][7][8][9]. Chromosome regions 4p15.1-q12 and 3p21 have also been identified as functional NPC susceptibility loci by linkage analysis of Chinese pedigrees [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that environmental factors such as the intake of salted food, Epstein-Barr Virus (EBV) infection, and the function of genetic factors were thought to be important in the etiology of NPC [3]. Loss of heterozygosity (LOH) studies unveiled there are frequent allelic losses on chromosomes 3p, 9p, 11q, 13q, and 14q in NPC [4][5][6][7][8][9]. Chromosome regions 4p15.1-q12 and 3p21 have also been identified as functional NPC susceptibility loci by linkage analysis of Chinese pedigrees [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…We used 5 0 UTR of LINE-1.2 sequence from NCBI Accession Number M80343. DNA isolation and extraction from leukocytes, sera, and unstained microdissected paraffin-embedded tissues and treatment with bisulfite have been described previously (Herman et al, 1996;Xiong and Laird, 1997;Mutirangura et al, 1998Mutirangura et al, , 1999. Bisulfited DNA was subjected to 35 cycles of PCR with two primers, 5 0 -CCGTAAGGGGTTAGGGAGTTTTT-3 0 and 5 0 -RTAAAACCCTCCRAACCAAATATAAA-3 0 , with an annealing temperature of 501C.…”
mentioning
confidence: 99%
“…While the identification and isolation of specific TSGs in NPC development is still forthcoming, molecular studies utilizing microsatellite typing and loss of heterozygosity (LOH) approaches implicate the involvement of TSGs residing on chromosomes 3,9,11,13,14, and 16 in NPC. [28][29][30][31][32][33][34][35][36][37][38][39] High frequencies and consistent occurrence of LOH on chromosomes 3, 9, 13, and 14, in particular, highlight the importance of the candidate TSGs mapping to these chromosomes in NPC. Conventional cytogenetics and current comparative genomic hybridization (CGH) data support these molecular findings concerning involvement of numerous regions of multiple chromosomes in NPC.…”
Section: Genetic Basis For Nasopharyngeal Carcinomamentioning
confidence: 99%